A new species of Phasmatocoris Breddin (Hemiptera: Reduviidae: Emesinae) from the Amazon, Brazil - Gil-Santana, Hélcio R.; Alves, Veracilda Ribeiro; Barrett, Toby Vincent; Costa, Luiz A.a. (Zootaxa, 2007)
Phasmatocoris xavieri sp. nov. is described based on male and female adults and a last-stage nymph. The specimens were found on the walls and roof of a cave named “Gruta dos Animais” (02°03´02,64S/59°57´51,47W), a sandstone cave located in primary “terra firme” forest to the north of the city of Manaus, Amazonas State in Brazil. The individuals were about 30m from the entrance, in an aphotic zone. Adults share characteristics with the species Phasmatocoris magdalenae Wygodzinsky, P. sturmi Wygodzinsky, and P. moraballi Wygodzinsky.